Oral Presentation No. 81 A STEMI case with sub-occlusive lesion and high thrombotic burden – discussing a tailored approach. (21st October 2022) - Lima, Maria Rita; Raposo, Luís; Albuquerque, Francisco; Oliveira, Afonso Félix; Almeida, Manuel; Abecasis, João; Mendes, Miguel
Abstract: A 57-year-old man was admitted with an anterior wall STEMI. The patient had a past medical history of pulmonary thromboembolism after an abdominal surgery and peripheral artery disease. After receiving loading doses of aspirin and unfractionated heparin, the patient underwent emergent coronary angiography (CA), that revealed a high thrombotic sub-occlusive lesion in the middle left anterior descending artery (mLAD), with TIMI 3 flow. At the time of CA, the ST elevation had disappeared, and the patient was asymptomatic. PCI had the risk of distal embolization and wiring of the false lumen if a dissection was present. Given the patient stability and absence of pain, the team decided to optimize anti-thrombotic therapy - aspirin + ticagrelor + enoxaparin - and repeat the CA within 72–96 h. The patient remained asymptomatic without angina or heart failure. Repeated CA showed a significant reduction of thrombus in the mLAD, maintaining TIMI 3 flow. A non-obstructive lesion was noted, being unclear if there was plaque rupture or localized dissection. Coronary CT angiography (CCTA) showed a coronary calcium score of 0 and an endoluminal flap in the mLAD, with a partial non-obstructive thrombosis. Echocardiography showed preserved LVEF without segmental abnormalities. Given the good results of anti-thrombotic therapy, the patient was discharged with aspirin, clopidogrel and rivaroxaban 2.5 mg 2id for 2 months and PCI was not performed. A follow-up CCTA within 2 months was scheduled. This case illustrates a complex STEMI case with a high thrombotic burden. The best strategy in such cases is open to debate.